THE UNIQUENESS OF EXPRESSION OF EDUCATIONAL MOTIVES IN STUDENTS - Karimjonova Yoqutxon (Journals Park Publishing, 2023)
Motives control the process of reading and learning, determine the content and essence of education along with the acquisition of activity. Therefore, in the process of education of students, educational motivations and comprehensive motivations are of great importance in the formation of a well-rounded person, a mature qualified staff.